Antioxidant activities, total phenolic and flavonoid content in small size cultivar and large size cultivar of Centella asiatica / Muhammad Saddam Hussein Alias - Alias, Muhammad Saddam Hussein (2015)
Free radicals is the unstable molecules that can damage the cells. Free radical occurs from the digestion of food or breathing in polluted air. In order to protect cells in body from free radical, antioxidant is the nutrient that help to prevent from damaging of the cells. Antioxidant can be founded in food or supplementation. The damaging of cells may increase the risk of getting cancer, heart disease, diabetes, or infections. Therefore, the need for antioxidants becomes even more critical with increased exposure to free radicals. In industries, the synthetic antioxidant is widely used such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA) even thought it could lead to negative health effect. In recent years, a lot of herbal medicine is used as the alternative therapy. Centella asiatica has been claimed that have many physiological effect and its traditionally used. However, there was lack of data reported on antioxidant activity using Centella asiatica fresh extraction. Thus, in this study is focusing on antioxidant activities of 1, I-diphenyl2- picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Potential (FRAP), total phenolic contain (TPC) and total flavonoid content (TFC) in small size cultivar and large size cultivar of Centella asiatica. At the end ofthe experiment, the TFC has shown increase in antioxidant activity of small cultivar and large cultivar with value 489.84 quercetin equivalent Ig extract and 350 quercetin equivalent Ig extract, compare to the control (p<0.05). On the other hand, the correlation study show the DPPH and FRAP is highly correlated with TPC and TFC. In conclusion, this finding suggested that Centella asiatica possesses antioxidant activity.